Blood-Based miRNA Biomarkers as Correlates of Brain-Based miRNA Expression - Kos, Mark Z.; Puppala, Sobha; Cruz, Dianne; Neary, Jennifer L.; Kumar, Ashish; Dalan, Emma; Li, Cun; Nathanielsz, Peter; Carless, Melanie A. (Frontiers in Molecular Neuroscience, 2022)
The use of easily accessible peripheral samples, such as blood or saliva, to investigate neurological and neuropsychiatric disorders is well-established in genetic and epigenetic research, but the pathological implications of such biomarkers are not easily discerned. To better understand the relationship between peripheral blood- and brain-based epigenetic activity, we conducted a pilot study on captive baboons (Papio hamadryas) to investigate correlations between miRNA expression in peripheral blood mononuclear cells (PBMCs) and 14 different cortical and subcortical brain regions, represented by two study groups comprised of 4 and 6 animals. Using next-generation sequencing, we identified 362 miRNAs expressed at ≥10 read counts in 80% or more of the brain samples analyzed. Nominally significant pairwise correlations (one-sided P<0.05) between peripheral blood and mean brain expression levels of individual miRNAs were observed for 39 and 44 miRNAs in each group. When miRNA expression levels were averaged for tissue type across animals within the groups, Spearman’s rank correlations between PBMCs and the brain regions are all highly significant (rs=0.47-0.57; P<2.2x10-16), although pairwise correlations among the brain regions are markedly stronger (rs=0.86-0.99). Principal component analysis revealed differentiation in miRNA expression between peripheral blood and the brain regions for the first component (accounting for ~75% of variance). Linear mixed effects modeling attributed most of the variance in expression to differences between miRNAs (>70%), with non-significant 7.5% and 13.1% assigned to differences between blood and brain-based samples in the two study groups. Hierarchical UPGMA clustering revealed a major co-expression branch in both study groups, comprised of miRNAs globally upregulated in blood relative to the brain samples, exhibiting an enrichment of miRNAs expressed in immune cells (CD14+, CD15+, CD19+, CD3+, and CD56+ leukocytes) among the top blood-brain correlates, with the gene MYC, encoding a master transcription factor that regulates angiogenesis and neural stem cell activation, representing the most prevalent miRNA target. Although some differentiation was observed between tissue types, these preliminary findings reveal wider correlated patterns between blood- and brain-expressed miRNAs, suggesting the potential utility of blood-based miRNA profiling for investigating by proxy certain miRNA activity in the brain, with implications for neuroinflammatory and c-Myc-mediated processes.